STUDIES REGARDING THE PRESENCE OF THE PATHOGENS BACTERIA INTO A RECIRCULATING SYSTEM OF BELUGA STURGEON INTENSIVE REARING - ANGELICA DOCAN; IULIA GRECU; LORENA SFETCU; I. VASILEAN; V. CRISTEA (Scientific Papers Animal Science and Biotechnologies, 2023)
Recirculating aquaculture offers good potential for successful fish farming since is often independent of environmental conditions. Maintaining healthy fish in a recirculating system involves establishing adequate dissolved oxygen levels, removal of solid wastes, and sufficient ammonia nitrification to assure optimal rearing conditions. Neglecting these, the fish immune system will depress, the facultative pathogen germs will be able to provoke important disease outbreaks into cultured biomass, as was happened in our recirculating pilot system. In this study are presented the pathological aspects registered to the beluga sturgeon of 1 year, reared into our recirculating pilot system, pathological aspects generated by a haemorrhagic bacterial septicaemia which was manifested in the conditions of low concentrations of DO. The disease was diagnosed to the affected fish through anatomopathological and clinical exam, haematological exam and microbiological exam.